Neurodegeneration: can metabolites from Eremurus persicus help? - Cavalloro, Valeria; Marchesi, Nicoletta; Linciano, Pasquale; Rossi, Daniela; Campagnoli, Lucrezia Irene Maria; Fossati, Alice; Ahmed, Karzan Mahmood; Malacrida, Alessio; Miloso, Mariarosaria; Mazzeo, Giuseppe; Abbate, Sergio; Longhi, Giovanna; et al. (Frontiers in Pharmacology, 2024)
The number of patients affected by neurodegenerative diseases is increasing worldwide, and no effective treatments have been developed yet. Although precision medicine could represent a powerful tool, it remains a challenge due to the high variability among patients. To identify molecules acting with innovative mechanisms of action, we performed a computational investigation using SAFAN technology, focusing specifically on HuD. This target belongs to the human embryonic lethal abnormal visual-like (ELAV) proteins and plays a key role in neuronal plasticity and differentiation. The results highlighted that the molecule able to bind the selected target was (R)-aloesaponol-III-8-methyl ether [(R)-ASME], a metabolite extracted from Eremurus persicus. Notably, this molecule is a TNF-α inhibitor, a cytokine involved in neuroinflammation. To obtain a suitable amount of (R)-ASME to confirm its activity on HuD, we optimized the extraction procedure. Together with ASME, another related metabolite, germichrysone, was isolated. Both ASME and germichrysone underwent biological investigation, but only ASME confirmed its ability to bind HuD. Given the multifactorial nature of neurodegenerative diseases, we decided to investigate ASME as a proteasome activator, being molecules endowed with this kind of activity potentially able to counteract aggregations of dysregulated proteins. ASME was able to activate the considered target both in enzymatic and cellular assays. Therefore, ASME may be considered a promising hit in the fight against neurodegenerative diseases.